-16=4(f+6)

Simple and best practice solution for -16=4(f+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16=4(f+6) equation:



-16=4(f+6)
We move all terms to the left:
-16-(4(f+6))=0
We calculate terms in parentheses: -(4(f+6)), so:
4(f+6)
We multiply parentheses
4f+24
Back to the equation:
-(4f+24)
We get rid of parentheses
-4f-24-16=0
We add all the numbers together, and all the variables
-4f-40=0
We move all terms containing f to the left, all other terms to the right
-4f=40
f=40/-4
f=-10

See similar equations:

| 16k-5k+2k-7k-4k+2=8 | | 1/2q-2=3/2q | | 2(x-1)+3(x-2)+4(x-3)=3(x-1) | | 4+10=-2(7x-7) | | x+9=-51 | | -10z+18+4z=2(z-3) | | 15x−4+40x=25−3x | | X+2y=2.25 | | 8=h+4 | | -11w=-132 | | 55+4-2x+x=180 | | 14+8r=6r+38 | | -8=6-q | | 3(m-4)+5=-4 | | 7h−7=6h | | 1+6x-x=9 | | -7x+10=4x-20 | | -9=f/2-11 | | X+2(x)=2.25 | | 4(-3n-6)=-6(n-2 | | 6x–12=3x+18 | | 5x+180=15x | | -17+27=-5(x+6) | | (-2x/3)+2=42 | | -2x+2(-5)=-11 | | -4w+3=-5w | | 1/4096=1/2^x | | 4x+5=10x+7=40 | | -22-3r=5r-2 | | 9x-20=3x-3 | | –6w=7−5w | | -4(-4n-7)=36+8n |

Equations solver categories